PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI PENGEMBANGAN KELOMPOK WANITA PENGUSAHA “KAMPUNG KUE” DI DESA CEWENG, KECAMATAN DIWEK, KABUPATEN JOMBANG - Kristin, Juwita; Mutiarni, Rita (COMVICE: Journal Of Community Service, 2025)
Community Service is an implementation of the Tri Dharma of Higher Education that focuses on improving community welfare through collaboration between academics and local communities. This program aims to enhance the economic capacity of society through the development of the Women Entrepreneurs Group “Kampung Kue” in Ceweng Village, Diwek District, Jombang Regency. Most of the members are housewives running small traditional businesses facing challenges in business management, digital marketing, and product innovation. The activity was conducted in April 2025, involving 30 active participants through a participatory approach. The main activities consisted of financial management training, digital marketing workshops using social media, and product packaging innovation guidance to improve attractiveness and hygiene. The results indicated significant improvement in participants’ entrepreneurial skills, digital marketing capabilities, and product quality. This program contributes to women’s economic independence in rural areas and is expected to become a model of sustainable community-based economic empowerment.